The Use of English Songs to Improve EFL Students’ Pronunciation - Sambonu, Febiola; Rofiqoh, Rofiqoh; Erniwati, Erniwati (International Journal of Language Teaching and Education, 2025)
The purpose of this study is to demonstrate whether providing grade eight students at SMP Negeri 1 Poso Pesisir Selatan with English songs may enhance their pronunciation. In contrast to the sounds in Indonesian, this investigation focused on the dental and palato-alveolar fricative sounds. In this quasi-experimental study, data from both the experimental and control groups were used, including pre-test and post-test results. Passing the pronunciation test required students to enunciate minimal pairs. Six treatment sessions were conducted with the experimental group, with the primary goal of listening to and practicing the pronunciation of specific songs. The results showed improvement in pronunciation ability, with a p-value of 0.000 < 0.05, and the average score increased after the treatment. This study offers practical implications for English teachers to integrate engaging media into pronunciation instruction, encouraging better articulation and fluency. The findings suggest that English songs can serve as effective learning media to improve students' English pronunciation.